A Novel In Vivo Quantitative Assessment of the Knee Using High Resolution Peripheral Quantitative Computed Tomography - Kroker, Andres; Manske, Sarah; Zhu, Ying; Barber, Rhamona; Mohtadi, Nicholas; Boyd, Steven (CMBES Proceedings, 2016)
INTRODUCTION: Anterior cruciate ligament (ACL) tears are a common knee injury and increase the risk of developing osteoarthritis (OA). While the sequence of events leading to OA is poorly understood, evidence suggests rapid changes in subchondral bone mineral density (BMD) in the injured knee after the ACL tear may play a role. How these changes are reflected in the bone microarchitecture is not understood, largely because clinical imaging modalities lack the required resolution to visualize the microarchitecture. High resolution peripheral quantitative computer tomography (HR-pQCT), a novel human in vivo micro computed tomography system, is able to measure bone microarchitecture. METHODS: Thirty-five participants were imaged with HR-pQCT at an isotropic resolution of 61 µm after undergoing varying types of ACL reconstructions five year prior. Approximately 6 cm of each knee was imaged. The medial and lateral weight bearing regions of both tibia and femur were analyzed. The subchondral bone in these regions was isolated and trabecular thickness, number, and BMD were measured at three depths (0-2.5mm, 2.5-5mm, 5-7.5mm) below the subchondral bone surface as well as cortical thickness and porosity. RESULTS: Scans took approximately 22 minutes per knee and provided rich 3D data showing bone morphology and microarchitecture. Bone microarchitectural parameters were successfully calculated for all regions and depths. CONCLUSIONS: We performed the first in vivo high resolution bone microarchitecture measurements of the human knee. Ongoing work includes establishing quantitative differences between lateral and medial bone compartments in the cohort, and characterizing differences between ACL deficient and healthy control knees. "